Entrepreneurial activities of Canadian Bangladeshi women in Toronto: a family perspective. - Akbar, Marshia; Preston, Valerie (Journal of Ethnic & Migration Studies, 2023)
Applying a family lens, the study illustrates how family resources and gender roles shape the entrepreneurship pathways of immigrant women. With its focus on the family, the study contributes to intersectional research about immigrant entrepreneurs that considers the effects of gender and social class, as well as, ethnicity. Drawing on the narratives of Bangladeshi women who migrated to Toronto as spouses of skilled male immigrants, the research examines their decisions to start and operate home-based and non-home-based businesses. Though similar employment barriers faced many Bangladeshi couples in Toronto, gender roles and family resources influenced the women's strategies to combat economic marginalisation and loss of middle-class status. The home-based businesses operated by Bangladeshi women required little financial capital and offered services and goods produced with domestic resources while the non-home-based businesses operated by Bangladeshi women often complemented existing family enterprises.